Implementation of the Role Playing Method on the Exemplary Stories of the Walisongo to Increase the Enthusiasm of MI Students in Learning - Nadya Muliya Purnamahawati; Khairunisa Ramadani; Safa Riska Fajriani; Tazkia Ardani; Elisa Ikmah; Diva Aulia Putri; Shilvia Ariana Putri; Dian Rif’iyati (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This research aimed to assess the effectiveness of the Role-Playing technique in the instruction of Islamic cultural history. The approach chosen was a Literature Review, which involves exploring and examining numerous sources by studying books, academic journals, and other written materials. The findings presented in this article suggest that utilizing this method in education greatly benefits both instructors and learners. This is due to the fact that the method acts as a facilitator in the educational process, helping to achieve the desired learning objectives. The positive influence on educational success is quite evident. From the Literature Review, it can be inferred that implementing the role-playing technique is a vital element in achieving educational success, as this method enhances the presentation of content, particularly in the realm of Islamic Cultural History. This study indicates that this approach has effectively boosted student engagement, learning achievements, and results by promoting a more organized and effective teaching strategy.